SIFAT PAPAN SERAT DARI KAYU ACACIA MANGIUM WILLD., EUCALYPTUS DEGLUPTA BLUME DAN EUCALYPTUS UROPHYLLA BLAKE - Kayano Purba; Deden Edi Rusfiandi; Yusuf Sudo Hadi; M Rosid (Jurnal Penelitian Hasil Hutan, 1989)
This paper  deals  with  the  study   on  the  fiberboard   properties   of  A.  mangium,  E. deglupta and  E. urophylla.  The cooking  process  applied   consisted  of hot  caustic soda semi chemical process  and prehydrolysis   prior  to mechanical pulping process.The  hot  caustic  soda  semi  chemical  process   used  the  condition   as follows:   alkali  concentration    was 35 g/l,  wood  to liquor  ratio  was 1    :   8, maximum   temperature   was  100° C and  this  temperature   was kept  for two  hours.  The prehydrolisis prior  to  mechanical  process  was prepared   in the autoclave  with  the wood  to liquor  ratio ;of   .     1    :  8, maximum   temperature was  175  ± 1°C  and  this  temperature   was  kept   for  60  seconds,   and  the pressure  of  7 -   12 kg/cm2.      Sheet  forming  was done   by  wet  felting process  in the deckle box,   the pressing pressure  was 50  kg/cm2,      temperature   was 170° C for  10 mi- nutes.  Heat  treatment   was given for 3 hours at temperature  of  170° C without  pressure.The  result  shows  that  the  cooking  process  has a  significant   influences  on  the  moisture  content,   water  absorption, thickness   swelling,   tensile  strength  parallel  to  surface  and  modulus   of  rupture   of  the  fiberboard.   Likewise,   the  wood species  has a  significant   influence   on pulp  yield,   moisture  content,   water  absorption   and  thickness  swelling.  The interac- tion of  both  factors  only  significantly  influences   modulus  of rupture  and modulus  of elasticity.The  highest  pulp  yield  was from  A.  mangium  followed   by  E. deglupta,  and  E. urophylla.  Almost  overall properties of  fiberboard   met   the  FAO  standard,  except   for  the  water  absorption   and  tensile  strength  parallel  to surface  of  E. uro- phylla.  The  mechanical process   produced   fiberboard   with  better  water  absorption   and  thickness  swelling  than  that of hot caustic  soda  semi  chemical  process.   On  the  other  hand  the  tensile  strength  parallel  to surface  and  modulus   of  rupture of  the  fiberboard  produced    by  hot  caustic  soda  semi-chemical   process   was  found   better   than  that  of  the  mechanical pulping.